2021
DOI: 10.1177/0272684x20977366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training on HIV Risk Perception, Knowledge and Sexual Behaviour Among Fisherfolks in Two Communities in North Central Nigeria

Abstract: Fisherfolks participate in unsafe sexual behaviors which can predispose them to HIV infection. This research was designed to assess the effects of training on HIV/AIDS-related knowledge and sexual behavior among fisherfolks in two fishing communities in Nigeria. Respondents were allocated into Experimental Group (EG, n = 103) and Control Group (CG, n = 105). Data were collected at baseline using a questionnaire which included questions on socio-demographic characteristics, sexual behavior among others. A 3-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…According to Enahoro et al sexual activity among young people is a phenomenon that can no longer be considered as 'mere speculation' but need intervention [27]. "An intervention study have shown that training increased HIV/AIDS knowledge, improved risk perception and reduced risky sexual practices among study population" [28]. "Nevertheless, there is a general neglect of HIV/AIDS programmes in rural communities even though people living with HIV/AIDS often return to their rural communities after contracting HIV/AIDS in urban areas" [26].…”
Section: Introductionmentioning
confidence: 99%
“…According to Enahoro et al sexual activity among young people is a phenomenon that can no longer be considered as 'mere speculation' but need intervention [27]. "An intervention study have shown that training increased HIV/AIDS knowledge, improved risk perception and reduced risky sexual practices among study population" [28]. "Nevertheless, there is a general neglect of HIV/AIDS programmes in rural communities even though people living with HIV/AIDS often return to their rural communities after contracting HIV/AIDS in urban areas" [26].…”
Section: Introductionmentioning
confidence: 99%